PENGARUH KOMPETENSI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS ENERGI DAN SUMBER DAYA MINERAL KABUPATEN SIGI - Revita, Meri (Katalogis, 2015)
The type of the study is causal descriptive that shows relationship between variables studied by involving 31 respondents who are selected through sensus method. The Result based on multiple linear regressions analysis tests show that: 1) competency, work discipline, and work environment simultaneously have significant influence on the performance of employess in The Department of Energy and Mineral Resources, Sigi District; 2) competency has significant influence on the perfomance of employees in The Department of Energy and Mineral Resources of Sigi District; 3) work competency has significant influence on the perfomance of employees in The Department of Energy and Mineral Resources, Sigi District; 4) work environment has significant influence on the performance of employees in The Department of Energy and Mineral Resources, Sigi District.